Economic Transformation and Its Effects in Rural Areas - Jahan, Musharrat; Ali, Md Rahamat; Hossain, Md Uzzal; Abdullah-Al-Faisal, Md; Baksh, Md Awual (Journal of Bangladesh Institute of Planners, 2015)
‘Economic Transformation’ refers to a long-term and irreversible change in the prevailing economic activity. As the global economic trend is changing swiftly, Bangladesh economy is struggling to renovate itself to endure the competition while continuing to arrange for employment opportunities, alleviate poverty and increase economic growth. Our objective was to find out whether Baneshwar union of Puthia Upazila, Rajshahi faced any economic transformation and if so, how this transformation affected their rural lifestyle. We also provided recommendation to further the economic transformation. This study helped us conclude that- Economic transformation is a dynamic process in Baneshwar and most people have transformed to business sector. No transformation occurred in traditional occupation (example, pottery, etc.). Jaigir Para is least transformed locality. Increased economic transformation improved infrastructural situation and upgraded social facilities. Based on above findings we suggested that, Jaigir Para needs investment to prosper economically. Traditional occupations need investment so that they can be sustained. Although Baneshwar is a small union in the backward nor-western region of Bangladesh, it has shown promises of transformation and development and with a little help from authorities and benevolent organizations this union can go a far way towards productive growth and economic freedom. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 243-251